Follow-up household serosurvey in Northeast Brazil for zika virus: sexual contacts of index patients have the highest risk for seropositivity - Magalhaes, Tereza; Morais, Clarice N. L.; Jacques, Iracema J. A. A.; Azevedo, Elisa A. N.; Brito, Ana M.; Lima, Priscilla V.; Carvalho, Gabriella M. M.; Lima, Andreza R. S.; Castanha, Priscila M. S.; Cordeiro, Marli T.; Oliveira, Andre L. S.; Jänisch, Thomas; et al. (The journal of infectious diseases, 2021)
Our household-based serological survey for Zika and chikungunya viruses in Northeast Brazil suggests that sexual contact may be a strong driver of ZIKV exposure
Published online September 5, 2020
Gesehen am 30.06.2021